Draft Tenth Five Year Plan 2002-2007 Volume-I Introduction Union Territory of Lakshadweep - Planning Commission (Planning Commission, 2002)
The Union Territory of Lakshadweep is an archipelago of coral islands consisting of 12 atolls, 3 reefs and 5 submerged banks. There are in all 36 islands in this group, out of which 10 are inhabited, 21 uninhabited (and attached islets) and 5 are submerged banks. These beautiful and unpolluted islands having a total land area of 32 sq. kms. (useable land area being only 26 sq. kms.) lie at a distance of about 220 to 440 kilometers away from the west coast of Kerala in the Arabian Sea.
Union Territory of Lakshadweep, Planning and Statistics Department